Instant milk maker / Nur Ikhwan Mohd Noor … [et al.] - Mohd Noor, Nur Ikhwan; Mohd Rodzi, Siti Nurul Aini; Wan Abdull Hamid, Wan Norhanis Hanini; Faizul, Fatin Ayuni; Shamsul Kahar, Amalina (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
In the fast-paced world, most of the mothers want something that can save time and simplify everyday work. Because they are too busy with their work, most of the mothers think that prepare milk for their child is too complicated and time consuming. To solve this problem, mothers do not need to use the manual method with the milk mixing machine called 'Instant Milk Maker'. This machine works automatically and only takes a short time to prepare. It also features a touch screen to select a suitable measure of milk with the desired volume of water. Water temperature to provide milk was limited to 40°C, a temperature suitable for preparation of baby milk. This machine also uses a specially designed bottle with two sizes of medium and large sizes. With this machine, parents who have a baby should not take too long to provide milk for their baby. Market potential for this product is high because this machine has never been produced before. Target market for this machine is consists of working parents, soon-to- be parents, homemakers and carers (nursery).